2006
DOI: 10.1007/s10535-006-0060-y
|View full text |Cite
|
Sign up to set email alerts
|

Variability for the in vitro culture response in tomato recombinant inbred lines

Abstract: The aim of this work was to estimate genetic variability for in vitro culture response of recombinant inbred lines (RILs) of the genus Lycopersicon. The callus percentage (C), the regeneration percentage (R) and the productivity rate (PR) were evaluated 45 d after culture initiation in a set of 16 elite tomato RILs and their parents. The narrow sense heritability (h 2 ) values were 0.38 ± 0.04 for C, 0.46 ± 0.04 for R, and 0.28 ± 0.03 for R, while the genetic correlation (r g ) values were -0.96 ± 0.07 between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Cultivar 'Caimanta' of L. esculentum as the high regeneration capacity genotype (regeneration percentage = 87.93 ± 3.88) and accession LA722 of L. pimpinellifolium as the low regeneration capacity genotype (regeneration percentage = 34.44 ± 15.17) were selected based on previous results (Pratta et al 2006). Crosses were made to obtain F 1 (Caimanta · LA722) and both backcrosses (BC I = F 1 · LA722, and BC II = Caimanta · F 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cultivar 'Caimanta' of L. esculentum as the high regeneration capacity genotype (regeneration percentage = 87.93 ± 3.88) and accession LA722 of L. pimpinellifolium as the low regeneration capacity genotype (regeneration percentage = 34.44 ± 15.17) were selected based on previous results (Pratta et al 2006). Crosses were made to obtain F 1 (Caimanta · LA722) and both backcrosses (BC I = F 1 · LA722, and BC II = Caimanta · F 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Pratta et al (2006) evaluated the in vitro behavior of 16 recombinant lines derived from a crossing between the same progenitors used in this work. These authors found a narrow sense heritability value important for callus percentage as well as for regeneration percentage, which can be explained by the expected changes in the genetic variance composition (that is, an increase in the additive component) throughout successive cycles of self-fertilization.…”
Section: Prmentioning
confidence: 99%
See 1 more Smart Citation
“…The selective amplification samples were prepared using 5 μL of this dilution and the same components mentioned earlier. Three primer +3 combinations reported by Pratta et al (2006) were used: A combination: 5 -GACTGCGTACCAATTCAGA-3 / 5 -GAT GAGTCCTGAGTAACTA-3 ; B combination: 5 -GACTGC GTACCAATTCAGC-3 / 5 -GATGAGTCCTGAGTAACAT-3 ; N combination: 5 -GACTGCGTACCAATTCATC-3 / 5 -GATGAGTCCTGAGTAACAT-3 .…”
Section: Molecular Characterizationmentioning
confidence: 99%